ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL) PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2014–2016 - Rodiyah, Siti (Universitas Nahdlatul Ulama Surabaya, 2018)
This study aims to determine how the health of Sharia Commercial Banks using RGEC method. Data analysis technique used in this research is RGEC method and financial statement analysis. The type of qualitative descriptive research with quantitative data. The assessment factors on RGEC method are: risk profile using measurement indicators on credit risk factor (NPF) and liquidity risk (FDR), good corporate governance using data that has been processed and obtained from each sharia bank (self-assessment result), earnings using measurement indicators on ROA, NIM, ROE, and BOPO, capital using measurement indicators on CAR. The results of this study indicate that banks that have healthy health status in 2014 to 2016 are BCA Syariah and BNI Syariah. While banks that are in fairly healthy condition consistently period 2014 until 2016 is Bank Muamalat and Bank Victoria Sharia. While other banks the level of health is quite volatile ie in a healthy and quite healthy.